Sketching MLS Image Deformations On the GPU - Weng, Yanlin; Shi, Xiaohan; Bao, Hujun; Zhang, Jun (Computer graphics forum, 2008)
In this paper, we present an image editing tool that allows the user to deform images using a sketch‐based interface. The user simply sketches a set of source curves in the input image, and also some target curves that the source curves should be deformed to. Then the moving least squares (MLS) deformation technique [SMW06] is adapted to produce realistic deformations while satisfying the curves' positional constraints. We also propose a scheme to reduce image fold‐overs in MLS deformations. Our system has a very intuitive user interface, generates physically plausible deformations, and can be easily implemented on the GPU for real‐time performance.